MISCELLANEOUS BOTANICAL NOTES XXVI - C. G. G. J. VAN STEENIS; J. F. Veldkamp (REINWARDTIA, 1982)
Description of the pod of the type tree of Ormosia incerta Koord. (reduced to 0. psnangensis Ridl.) from Java. Reduction of the genus Trifidacanthus Merr. (Legum.) to Desmodium; one new combination necessary. The genus Platyspermation Guillaumin described from New Caledonia in Myrtaeeae, suggested to belong to Saxifragaceae-Escallonioidsae. Juncus bufonius L. recorded as introduced on Mt Kinabalu. Two Fimbristylis species recorded new for the Northern Territory, Australia; Oreobolus kukenthalii Steen. recorded from Mt Muln, Sarawak.